Penerapan Tes Esei Pemetaan Konsep dan Gaya Kognitif dalam Pembelajaran IPA di Sekolah Dasar - Edi Kusnadi (Sekolah Dasar : Kajian Teori dan Praktik Pendidikan, 2009)
Abstract: The research aims at investigating a concept mapping test in science learning and elementary school students’ cognitive styles. A sample of 124 elementary school students in Metro Lampung was drawn randomly. The study revealed that the students’ learning outcomes treated with the concepts of mapping essay test are higher than those treated with the multiple choice test; the learning outcomes of the convergent students’ cognitive style are higher than those of the divergent students’ cognitive  style; there is an interaction effect between the formative assessments and the cognitive style toward the students’ learning outcomes; the learning outcomes of the convergent students’ cognitive style treated with the concepts mapping essay test are higher than those treated with the multiple choice; and the learning outcomes of the divergent students’cognitive style treated with the concepts mapping essay test are lower than those treated with the multiple choice test.